Cardiometabolic risk assessment in Eastern Slovak young adults using anthropometric indicators - Michaela Zigová; Eva Petrejčíková; Marta Mydlárová Blaščáková; Jana Gaľová; Hedviga Vašková; Soňa Kalafutová; Miriama Šlebodová (Anthropological Review, 2023)
Introduction: Selected anthropometric indicators, such as anthropometric measurements, indices, or ratios could be reliable predictors of future cardiometabolic risk in primary prevention, especially in young adults.